The effect of radiation dose on CBCT measurements of maxillary gingival thickness - Hiba Khateeb; Eli E Machtei; Jacob Horwitz (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2022)
Purposes: 1. to measure Gingival Thickness (GT) both directly and with CBCT using various exposure times, and compare them. 2. to compare hard tissue measurements between different exposure times within each CBCT system. The study hypothesis was that accuracy of CBCT GT measurement is impaired when reducing exposure time. Methods: 8 fresh pig maxillae were utilized for each of two CBCT scan systems (SysA and SysB). Eight disposable dental needles were inserted into the gingival tissue of each jaw until reaching resistance from the underlying bone. A mark on each needle at its entrance point into the soft tissue was created using a permanent marker. Jaws were scanned twice, using low (RadL) and high (RadH) exposure times. The needles were extruded, and an electronic caliper was used to measure the length of the penetrated portion of the needle in mm (Cli). Radiographic GT was measured on cross sectional images, produced in the axial direcion of the 3D location of the needles (Rad) in two software systems (R and I). Descriptive statistics, t-test and ANOVA were performed. Significance was set at 5%. Results: Software I mean Cli was 2.22mm ±  0.54mm, RadL and RadH were 2.34mm ±  0.47mm and 2.34mm ±  0.52mm. Software R RadL and RadH were 2.16mm ±  0.50mm and 2.23mm ±  0.49mm, respectively. Using pairwise comparisons, both soft and hard tissue RadL and RadH were not statistically different. There was a good correlation between clinical and radiographic measurements of gingival thickness and essentially no significant difference between higher and lower radiation doses. Conclusions: Reducing CBCT radiation may be possible without affecting accuracy of radiographic gingival thickness measurements , thus opening the way to a wider utilization of CBCT in dentistry. Clinical relevance: Reducing radiation dose may enable a wider utilization of CBCT in dentistry.